2006
DOI: 10.1515/jpem.2006.19.s2.583
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate Treatment of Bone Fibrous Dysplasia in McCuneAlbright Syndrome

Abstract: One of the main features of McCune-Albright syndrome is bone fibrous dysplasia (BFD) often associated with severe clinical outcomes, such as bone pain, bone deformities and pathological fractures. Medical treatment with bisphosphonates started 15 years ago. Recent trials in pediatric patients with BFD have shown encouraging results. We evaluated long-term efficacy and safety of pamidronate treatment of BFD in children and adolescents with MAS. The drug was administered at 4 month-1 year intervals according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 22 publications
0
25
0
2
Order By: Relevance
“…Lala et al [13] showed that bisphosphonate treatment decreases the fracture rate and pain in FD. The pathogenesis of FD involves aberrant osteoblast differentiation, leading to the formation of abnormal bone and increased interleukin-6-induced osteoclastic bone resorption; these activities provide the rationale for treating patients with bisphosphonates [14].…”
Section: Discussionmentioning
confidence: 99%
“…Lala et al [13] showed that bisphosphonate treatment decreases the fracture rate and pain in FD. The pathogenesis of FD involves aberrant osteoblast differentiation, leading to the formation of abnormal bone and increased interleukin-6-induced osteoclastic bone resorption; these activities provide the rationale for treating patients with bisphosphonates [14].…”
Section: Discussionmentioning
confidence: 99%
“…Medical treatment with bisphosphonates such as pamidronate, used for over 15 years in adults, has now been found to be promising for pediatric patients on both a short- and long-term basis, significantly improving bone pain and decreasing fracture rate with minimal side effects [18,19,20]. After several operations we tried several courses of pamidronate treatment (i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…100,101 The use of bisphosphonates in children has shown a good short-term safety profile and is helpful in decreasing bone pain associated with fibrous dysplasia. The impact on long-term prognosis in terms a decreased lesion size, decrease rate of pathologic fracture and deformity is less clear.…”
Section: Treatmentmentioning
confidence: 99%